61 Diagnosing concealed brugada syndrome; a 5 year inherited cardiac centre registry. (5th October 2017) - Brennan, P; Kearney, A; Topley, R; Irwin, K; McCall, D; Muir, A
Abstract : Brugada syndrome (BrS) is associated with increased risk of cardiac arrest due to ventricular fibrillation and remains an important cause of sudden arrhythmic death syndrome (SADS). BrS is recognised by phenotypic electrocardiographic (ECG) patterns alongside specific clinical risk factors. The type 1 BrS pattern may either be spontaneous or concealed. Ajmaline, a class 1 C Sodium channel antagonist, is used to unmask the concealed pattern seen in BrS. We, retrospectively, reviewed all 231 patients that underwent ajamline provocation between 2011 and 2016. 59 (26%) patients had a concealed type 1 BrS pattern after ajmaline provocation. 105 patients with a family history of BrS were screened, in whom 38(36%) had a concealed pattern. Within this group 6 families had a history of overlapping Long QT Syndrome (LQTS). 61 patients screened had a family history of SADS. 5(8%) of these patients had a positive response. A further 12 patients were screened due to potential arrhythmic symptoms alongside borderline type 2 or 3 BrS patterns. 16 patients were referred after an aborted cardiac arrest (ACA), with 3(19%) of these patients having concealed BrS pattern after ajmaline provocation. 15(30%) of the patients with concealed BrS had an identifiable SCN5 A variant after serological genetic analysis. An A-ICD was inserted in 5(9%) patients with concealed BrS including all 3 patients with prior ACA and one patient with non-sustained monomorphic ventricular tachycardia (VT) detected via an implantable loop recorder (ILR). These patients remain free from VT and device-led therapy at present. An ILR was inserted in 9(17%) patients to further risk stratify patients with on-going potential arrhythmic symptoms. On ILR interrogation, 2 patients had episodes of non-sustained VT. Electrophysiological studies (EPS) were performed for diagnostic purposes, alongside ajmaline provocation, in 4(6.8%) of the patients with concealed BrS. 2 EPS were entirely negative. Ventricular fibrillation (VF) was induced in one study, and this patient currently awaits A-ICD insertion. The remaining EPS were negative. No cardiac adverse events occurred during or after ajmaline infusion. One patient had documented evidence of temporary cholestatic jaundice post administration, a recognised but rarely reported complication. All 59 patients with BrS remain free from sustained ventricular arrhythmias, ACA and sudden cardiac death (SCD) at this time. In conclusion, ajmaline provocation is a safe and important diagnostic test for BrS. The ACA and ventricular arrhythmic event rate was low in our patient cohort. There was a 26% diagnostic yield in those patients referred as part of familial BrS screening, similar to that seen in other registries. The presence of a SCN5 A variant was seen in 30% of those with concealed BrS which is higher than previously published yields ~20–25%. 19% of patients with a history of unexplained ACA had concealed BrS which is higher than that seen in the CASPER registry.